2013
DOI: 10.3389/fphys.2013.00158
|View full text |Cite
|
Sign up to set email alerts
|

Global change and human vulnerability to vector-borne diseases

Abstract: This e-book presents a collection of research and review articles related to the spread, control and basic understanding of vector borne diseases all over the world. It is well known that a multidisciplinary point of view is necessary in order to develop a global vision of this emergent problem. Therefore, in order to promote this holistic approach to the knowledge of vector borne diseases, this e-book contains a total of 19 collaborations of entomologists, epidemiologists, virologists, parasitologists, bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Quantitatively, our results corroborate existing knowledge about the role of rainfall and temperature in dengue transmission by showing increases in R 0 with increases in temperature and number of rainfall days [26, 27] (Supplementary Text). We also find an increase in population density is related to an increase in R 0 , when considering data from both cities separately (Supplementary Text).…”
Section: Discussionsupporting
confidence: 88%
“…Quantitatively, our results corroborate existing knowledge about the role of rainfall and temperature in dengue transmission by showing increases in R 0 with increases in temperature and number of rainfall days [26, 27] (Supplementary Text). We also find an increase in population density is related to an increase in R 0 , when considering data from both cities separately (Supplementary Text).…”
Section: Discussionsupporting
confidence: 88%
“…Many arboviruses vectored by mosquitoes (Diptera: Culicidae) have expanded their geographic range and managed to achieve greater expansion in areas where they did not exist before. Human movement, global trade, climate change, and availability of susceptible mosquito vectors has increased the introduction of diseases to populations that otherwise would have been safely out of reach [ 35 , 88 ]. In Morocco, as for the majority of North Africa and Middle East countries, the epidemiological situation of arboviruses remains poorly or even uncharacterized [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Travelers infected with dengue virus during their trip returning home may place the local population at risk wherever mosquito vectors are present[ 8 , 9 ]. Therefore, the required conditions for the occurrence of a dengue outbreak in countries where dengue is not endemic include i) the presence of dengue viruses through repeated introduction of imported cases, ii) a sufficient density of competent vectors above the threshold, iii) a sufficient number of susceptible population, and iv) a favorable climatic and environmental condition for dengue transmission[ 10 ]. Furthermore, numerous studies suggested an effect of climate on DENV transmission through changes in vector population size and distribution.…”
Section: Introductionmentioning
confidence: 99%